Preparation and characterization of monodisperse molecularly imprinted polymers for the recognition and enrichment of oleanolic acid. Issue 8 (April 2016) - Tang, Zonggui; Liu, Changbin; Wang, Jing; Li, Hongmin; Ji, Yong; Wang, Guohong; Lu, Chunxia
Abstract : Monodisperse molecularly imprinted polymers for oleanolic acid were successfully prepared by a precipitation polymerization method using oleanolic acid as a template, methacrylic acid as a functional monomer, and divinylbenzene/ethylene glycol dimethacrylate as a crosslinker in a mixture of acetonitrile and ethanol (3:1, v/v). The imprinted polymers and nonimprinted polymers were characterized by using scanning electron microscopy, Fourier transform infrared spectroscopy, and thermogravimetric analysis. The resulting imprinted polymers had average diameters of 3.15 μm and monodispersity values of 1.024. The results clearly demonstrate that use of ethanol as a cosolvent is indeed exceedingly effective in promoting the dissolution of oleanolic acid and in obtaining uniform microspheres. Molecular recognition properties and binding capability to oleanolic acid were evaluated by adsorption testing, which indicated that the imprinted polymers displayed optimal binding performance with a maximum adsorption capacity of 17.3 mg/g and a binding saturation time of 80 min. Meanwhile, the produced imprinted polymers exhibited higher selectivity to oleanolic acid than that for ursolic acid and rhein. Herein, the studies can provide theoretical and experimental references for the oleanolic acid molecular imprinted system.